2018
DOI: 10.1088/1757-899x/393/1/012123
|View full text |Cite
|
Sign up to set email alerts
|

The development of an experimental beam support with an integrated load cell

Abstract: Abstract. This article gives a detailed description of the development of an experimental sensor beam support with an integrated load cell, in this paper also named a smart support. The smart support is designed as a part of a beam bending experimental apparatus. For small universities, the financial effort needed to equip experimental mechanics labs is considered unjustified for the purpose of undergraduate mechanics classes. Thus the majority of experiments conducted in mechanics and similar classes are done… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…These tests are not only important for material testing but also essential for students to conduct experimental studies in laboratory. However, equipping laboratories with expensive test apparatus is very difficult especially for small universities (Pisačić et al, 2018). For example, the price of an electromechanical test apparatus which can be used in the pressure and tensile tests of the profiles can be up to € 25000 (160,000 TL).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These tests are not only important for material testing but also essential for students to conduct experimental studies in laboratory. However, equipping laboratories with expensive test apparatus is very difficult especially for small universities (Pisačić et al, 2018). For example, the price of an electromechanical test apparatus which can be used in the pressure and tensile tests of the profiles can be up to € 25000 (160,000 TL).…”
Section: Introductionmentioning
confidence: 99%
“…It has two tripod legs which act like fixed supports. The deflection is measured with a dial gauge placed at the middle of the material (Pisačić et al, 2018). Kareem (2012) reported that there are also various types of such apparatus produced and used in different countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation